Mythology effect on semantic construction in contemporary architecture - Abass Ali Hamza; Battol Muofaq Khdim (Iraqi Journal of Architecture and Planning, 2018)
Architecture, as with other arts Like painting, poetic, refer to its time , the mythologycontaining a rich symbols had the ability to paint Architecture field with this richness ...The level of symbolization in Architecture is a conceptual level with timing clear details .. the Research reviews the relationship between the ancient world mythology and concepts of Contemporary architecture with the Answering the question that ... can the designer success by mything his symbols as a story .The research then came to group of conclusions that represent by two aspects, first How to create a free sign and How to contain Mythologicalsigns in a new design.How can intellectual relations in the production adopter of the legendary symbols that have the capacity to generate systems rather symbolic "of the iconic images in order to deepen the connotations and open horizons interpretations of what is owned by the legendary mythological symbol of expressive possibilities, and this is the importance of research.Key words : mythology, Legend, Monetary mythological